THE EFFECTS OF DRYING TEMPERATURE ON THE STRUCTURE AND CORROSION RESISTANCE OF Cr3+-BASED CONVERSION COATINGS ON ZINC-COATED STEEL SURFACE - Thuy, Hoang Thi Huong; Thang, Le Ba; Nam, Truong Thi; Huong, Nguyen Thi Thanh; Son, Vuong Truong (Vietnam Journal of Science and Technology, 2015)
In this paper, we present results of drying temperature influence on the structure and corrosion  resistance of  Cr(III)–based conversion coatings on the surface of zinc-coated steel. The results show that the quality of Cr(III)–based conversion coatings is strongly influenced by the drying temperature, the appropriate drying temperature is about 80 oC, and drying at higher temperatures will reduce corrosion resistance durability and raise the cost of the production process.